Requirements Of Application The Internal Marketing Strategy In Public Transport Companies - معروف حسن; قاسم سامر; فياض لينا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to demonstrate the requirements for internal marketing in the General Company for the port in Lattakia Governorate. The researcher relied on the descriptive method, as the scientific material related to the subject of the research was collected by relying on previous Arab and foreign studies, Arab and foreign books, periodicals, pamphlets and conferences related to the subject of the study, in order to define all aspects of the phenomenon studied and learn about its reality on the ground, and the most important Arab and international experiences in this field were found. One of the most important results of the study was that the average of the responses of the sample members for the employee empowerment variable was 3.598, which indicates that the direct manager of the workers shows a serious interest in listening to their ideas and suggestions, and sets the task only and leaves them the freedom to make the necessary decisions on how to complete the work, and that the workers participate in the management in preparing Plans, strategies and goals, and the management provides them with opportunities for creativity and innovation during their work on the job according to the answers of the sample members.